(untitled) (Revista Archai, 2018)
The main aims of this article are to demonstrate the presence of two physiological conceptions of pleasure in the Hippocratic Corpus, pointing out the differences between them and conjecturing about the reverberation of one of them in Plato’s dialogue Gorgias. We can find in texts of Greek medicine a description of pleasure produced during sexual intercourse and another related to the occurrence of pleasure during nourishment. However, the second account, unlike the first one, is strongly marked by the notion of pleasure as replenishment. Identifying a physiological conception of pleasure featured by a process of filling in the Hippocratic Corpus is relevant because a very similar conception seems to be taken as starting point by Plato in his reflections on pleasure.